Correlation between Socio-economic Factors and Stress with Hypertension Cases during the Covid-19 Pandemic - Firanggi Z.A. Benu; Indriati A. Tedju Hinga; Eryc Z. Haba Bunga (Poltekkes Kemenkes Palu, 2023)
Hypertension is often referred to as The Silent Killer because it is the second leading cause of death after hear disease. Hypertension cannot be due to single cause but multifactorial causes, wherein many factors can be a risk for hypertension. This study aims to analyze the correlation between socio-economic factors and stress with hypertension cases during the Covid-19 pandemic at Sikumana Community Health Center. This was an analytical observational study with a case control design. The study samples involved 84 respondents who were assigned in the case and control groups consisting 42 respondents, respectively, or with a ratio of 1:1. Data were analyzed using the chi square test by calculating the OR value. The results of this study indicated that there was a correlation between income (p= 0.016; OR= 3.21; 95% CI 1.33-8.05), employment status (p= 0.029; OR= 2.91; 95% CI 1.20 -7.15), education level (p= 0.004; OR= 4.06; 95% CI 1.62-10.13) and stress (p= 0.000; OR= 8.17; 95% CI 3.05-21.91) with hypertension. It can be concluded that there was a correlation between socio-economic factors (income, employment status, and education) and stress with hypertension cases in the work area of Sikumana CHC, Kupang City. Provision of education related to diverse food consumption pattern and stress management must be increased.